Analisis Faktor Socioeconomic Status (SES) Terhadap Kesehatan Mental: Gejala Depresi di Indonesia - Dewi, Yustika; Relaksana, Riki; Siregar, Adiatma Y. M. (UI Scholars Hub, 2020)
According to the World Federation of Mental Health, 1 of 5 people in the world experiences a mental disorder. Several studies have mentioned that one of the primary factors that cause mental disorders is the low of socioeconomic status in developing countries. Therefore, this study was conducted to determine the influence of socioeconomic status factors on depressive symptoms as a mental disorder, in one of the developing countries, Indonesia. This study uses a quantitative method based on secondary data taken from the Indonesia Family Life Survey (IFLS) wave 5 using the CESD-R 10 questionnaire for depressive symptom variables. Depression symptom variables obtained from IFLS 5 were first processed using the Rasch Model, then all variables were processed using the logistic regression method. As a result, the socioeconomic status factors are negatively correlated and have a significant influence on depressive symptoms in Indonesia, which means that socioeconomic status, in this case including the education, wealth, and work status, affects a person experiencing depressive symptoms.